Personal traits and skills as predictors of academic achievement: a study among the Bachelor of Information Studies (bis) and Bachelor of Administrative Science (bas) students of UiTM Kedah / Siti Hidayah Abd. Hamid - Abd. Hamid, Siti Hidayah (Faculty of Information Management, 2011)
Academic achievement is the quality of academic work measured by grade point average (GPA) or number of credits/courses completed or both. However, in order for a student to have an excellent GPA the students not only required to focus on academic but also the others factors such as the personality and their skills. Personal traits are enduring characteristics of the individual that summarize trans-situational consistencies in characteristic styles of responding to the environment. While the skill is the learned capacity to carry out pre-determined results often with the minimum outlay of time, energy, or both. Therefore, this study was conducted in order to identify on how the personal traits and skills can be predict as factor to the academic achievement of the Bachelor of Information Studies (BIS) and Bachelor of Administrative Science (BAS) students. A part from that this study try to emphasize on the awareness of the students on how important the personal trait and skills towards their success in their study and how this sets of skills can assist them in getting a good GPA. In this study the personal traits had been fracture into five broad factors which are the Extraversion, Neuroticism, Openness to Experience, Agreeableness, and Conscientiousness. While the skills had been break into the leadership skill, communication skill, Information technology skill and reading skills.